Evaluation of adverse events and comorbidity exacerbation following the COVID-19 booster dose: A national survey among randomly-selected booster recipients. - Dvora Frankenthal; Miri Zatlawi; Ziv Karni-Efrati; Lital Keinan-Boker; Aharona Glatman-Freedman; Michal Bromberg (PLoS ONE)
Background Periodic vaccination against COVID-19 persists with a recommendation to vaccinate especially older people and the chronically ill. However, vaccination compliance is low, likely due to concerns regarding adverse events (AEs). Objective To systematically and proactively evaluate the occurrence, onset, duration, and severity of self-reported AEs and comorbidities exacerbations that appeared up to 21-30 days following the third (booster) Pfizer BNT162b2 vaccine dose, and to examine the associations between the occurrence of any AEs and sociodemographic and pre-existing comorbidities. Methods A cross-sectional telephone survey among a nationally representative sample of Israeli vaccinated adults aged ≥18 was conducted from September through October 2021. Sociodemographic data was extracted from the Ministry of Health vaccination database, and data on AEs and comorbidities were collected using a structured questionnaire. Results Overall, 2,049 participants completed the survey (71.4% response rate). A total of 1360 (66.4%) reported at least one AE following the booster vaccine. The most frequently reported AEs were local (55.7%) and mild systemic (48.6%) reactions (i.e., fatigue, headache, fever), followed by neurological (4.5%) and allergic (3.9%) reactions. Exacerbation of comorbidities following the booster dose was most frequently reported by individuals with autoimmune or mental conditions. Most local (80.1%) and systemic (69.5%) reactions lasted up to three days. Only 8.3% sought medical care. Menstrual changes were reported by 9.6% of women aged <54 years. The occurrence of any AEs was associated with younger age, female gender, higher socioeconomic status, and living in suburban communities. AEs were not associated with pre-existing comorbidities. Conclusion Most AEs were mild to moderate and transient. They were associated with younger age, but not with pre-existing chronic diseases. Since the primary target population for vaccination consists of older individuals and those with comorbidities, we believe the current findings may assist in reducing COVID-19 vaccine hesitancy among these populations.